Pseudo-Dionysius as Polemicist: The Development and Purpose of the Angelic Hierarchy in Sixth-Century Syria. By Rosemary A. Arthur - Louth, Andrew (The journal of theological studies, 2009)
This book seems to have several purposes, mostly indicated (though not equally) in the title. First of all, the purpose of the writings ascribed to Dionysios was polemical: although Dionysios decries polemic in one of the letters (ep. 7), his purpose is decidedly polemical, and the object of the polemic is principally monks who claim authority on the basis of mystical experience. Secondly, the background to Dionysios is to be found in a Syriac-speaking milieu; this objective is pursued intermittently, and Rosemary Arthur draws on her wide reading in Syriac literature, as well as lamenting that very little attempt has been made by scholars to follow up this affinity, which has been noted before.